2009
DOI: 10.1016/j.jcf.2009.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Very high-dose ergocalciferol is effective for correcting vitamin D deficiency in children and young adults with cystic fibrosis

Abstract: Approximately 10-80% of patients with Cystic Fibrosis (CF) have vitamin D deficiency. Obtaining therapeutic vitamin D levels has been a challenge for CF care providers using current recommended high-dose oral ergocalciferol (400,000 IU over 2 months). The objective of this study was to evaluate the safety and efficacy of a 2-week, very high dose ergocalciferol (700,000 IU over 14 days) repletion strategy in children and young adults with CF. As part of a quality improvement initiative, a prospective cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 4 publications
(7 reference statements)
1
16
1
Order By: Relevance
“…We found a striking improvement in vitamin D status at 1 week with a trend for improved status over 12 weeks. As has been observed in other studies of high dose vitamin D, we found no adverse effects relating to hypervitaminosis D or hypercalcemia in the vitamin D group 2 , 17 , 18 …”
Section: Discussionsupporting
confidence: 90%
“…We found a striking improvement in vitamin D status at 1 week with a trend for improved status over 12 weeks. As has been observed in other studies of high dose vitamin D, we found no adverse effects relating to hypervitaminosis D or hypercalcemia in the vitamin D group 2 , 17 , 18 …”
Section: Discussionsupporting
confidence: 90%
“…Since multiple studies have demonstrated a high prevalence of vitamin D insufficiency, various repletion strategies are being studied in an attempt to find the appropriate repletion and maintenance strategy for vitamin D deficiency in CF patients [22][23][24][25]. One option which is gaining support is to use vitamin D 3 (cholecalciferol) instead of vitamin D 2 (ergocalciferol) in repletion regimens since vitamin D 3 may be more effective [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Because the range between the perceived normal vitamin D25(OH) starting point of 20 ng/mL and the higher level of 32 ng/mL remains an issue of debate, some have termed all serum vitamin D25(OH) values ,32 ng/mL as subtherapeutic (13). For this study, we considered serum vitamin D25(OH) values ,32 ng/mL to be subtherapeutic, levels specifically ,20 ng/mL insufficient, and those ,12 ng/mL deficient.…”
Section: Introductionmentioning
confidence: 99%